Reflection seismic with DAS, why and where? - Urosevic, Milovan; Bona, Andrej; Ziramov, Sasha; Martin, R.; Dwyer, J.; Foley, A. (2018)
© 2018 European Association of Geoscientists and Engineers, EAGE. All rights reserved. During the last decade the Distributed Acoustic Sensing (DAS) data acquisition has been tested in boreholes in a soft rock environment with a variable success. The technology is now approaching its maturity and it is showing a high potential. In hard rock environment however its use is much more challenging. In this study we show the first attempt to use this technology for surface reflection seismic rather than it is commonly attempted in boreholes. The principal reason is that in some specific environments such as a hyper-saline lakes, under which significant mineral reserves are found in Australia, the use of conventional equipment is limited and prone to significant hardware issues and equipment damage. In contrast such an environment seems appropriate for the application of the DAS technology. This study reports on the results from a comparative DAS-geophone surface reflection experimental survey conducted along a salt lake in Western Australia and shows that DAS has the potential to replace surface geophones in such environment.